CLASSIFICATION OF HYPERTENSIVE DISEASE IN PREGNANCY - Saona Ugarte, Pedro (2015)
Hypertension in pregnancy is a relative frequent disease, responsible of increased perinatal and maternal morbidity and mortality. Not all patients with hypertension in pregnancy will have similar prognosis. Establishing a unique classification system will allow professionals to use similar therapeutic and prognostic criteria. Different classification systems and terms have been proposed. In this article hypertension diagnosed previous to pregnancy or persisting more than 12 weeks after delivery is termed chronic hypertension. When hypertension is diagnosed after 20 weeks gestation it can be classified as gestational hypertension -when high blood pressure is the only clinical sign- or pre-eclampsia, a  multisystemic syndrome in which hypertension and proteinuria are the most frequent clinical manifestations; its diagnosis must also be considered if there are other organs or systems affected even without  proteinuria. Eclampsia will be diagnosed if seizures occur in patients with pre-eclampsia. Finally pre-eclampsia superimposed on chronic hypertension will have the worst prognosis.